A Study on the Protection of Terraced Agricultural Land Based on Local Wisdom in Argapura, Majalengka Regency - Sudrajat Sudrajat (Universitas Negeri Medan, 2026)
Currently, the role of local wisdom in agricultural land protection practices appears to be diminishing due to modernization, generational changes, and shifts in agricultural production orientation, posing a challenge to the sustainability of agriculture. This study aims to: (1) examine the types of land degradation occurring in terraced lands; (2) analyze the types of local wisdom-based land protection practices still applied by terraced land farmers; and (3) assess the influence of local wisdom-based land protection on the productivity of terraced agricultural land. From a population of 504 farmers, a sample of 100 was selected using Slovin’s formula with a 10% margin of error through simple random sampling. Additionally, 10 key informants were included, comprising farmers, farmer group leaders, and village officials. Primary data were collected using semi-structured questionnaires and in-depth interviews with informants. Sensitivity tests were conducted to ensure data consistency and validity. Data were processed using SPSS 28, and the results were presented in graphs and analyzed using descriptive qualitative methods, supported by findings from in-depth interviews. The study found that soil erosion and micro-landslides on terrace embankments are the most dominant types of land degradation experienced by farmers, which significantly affect agricultural productivity. To address these issues, farmers implement local wisdom-based land protection practices, including constructing bench terraces, using organic fertilizers derived from agricultural waste, collaboratively repairing irrigation channels, and prohibiting the burning of waste. Empirically, these practices have been able to maintain and even improve agricultural productivity.